Effect of a history of 3+ previous concussions on centre of pressure variables during quiet stance. Issue 11 (25th May 2017) - Dierijck, Jill K; Wright, Alexander D; Bryk, Kelsey; Smirl, Jonathan D; Donkelaar, Paul van
Abstract : Objective: To determine the influence of a history of 3+ previous concussions on quiet stance. Design: Retrospective cohort. Setting: Laboratory. Participants: Eighty-seven male (age range 17–22) contact-sport athletes (football and hockey) entered the study. Participants were recruited from the same sport teams and tested during the pre-season. Exclusion criteria: concussion in the prior 6 months, or history of 1 or 2 concussions. Forty-four met the inclusion criteria: thirty-one had no previous concussions, and thirteen had a history of 3+ concussions. Interventions: Participants held quiet upright stance on a force plate (NDI True Impulse) with feet hip-width apart and hands on hips with eyes-open (1 min), and closed (1 min). Independent variables included condition (2) and concussion history (2). Outcome measures: Root-mean-square displacement (RMSd), and mean velocity of centre-of-pressure (COP) in the anterior/posterior (AP) and medial/lateral (ML) directions. Main results: Mixed ANOVA indicated a significant condition effect in ML-RMSd (p=0.015, 95% CI: 0.032–0.277) between eyes-open and eyes-closed conditions. ML mean velocity also displayed a significant condition effect (p=0.025, 95% CI: 0.025–0.358). In contrast to the effect of visual input, there was no main effect of concussion history on these metrics. Conclusions: A history of 3+ concussions does not appear to result in long-term deficits controlling in quiet stance. Those ML variables were sensitive to condition and indicate that frontal plane COP movements may be more sensitive than those in the sagittal plane. These findings are important as a history of concussion does not appear to alter quiet stance balance control mechanisms. Competing interests: None.